TRANSFORMASI DIGITAL DESA: MEMPERKENALKAN OPENSID SEBAGAI SOLUSI PEMBUATAN WEBSITE DESA KEDUNGDOWO - suksma, Cahaya; Ramadhanti, Adinda; Agus H, Mahendra (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2024)
Digital transformation of villages has become a primary focus in rural development today. This article introduces OpenSID as a solution for website development in Kedungdowo Village. OpenSID is an open-source platform specifically designed for building and managing village websites. The article discusses the implementation process of OpenSID in Kedungdowo Village as part of its digital transformation. The steps involved in creating a village website, such as theme selection, information structure setup, and integration of relevant features, are explained in detail. OpenSID offers advantages in usability, flexibility, and adaptation to the village's needs. By utilizing OpenSID, Kedungdowo Village can create an informative, interactive website that is easily accessible to the community. The village website enables residents to access information about public services, and event agendas, and participate in village decision-making through online complaint and discussion features. The article also highlights the benefits derived from the implementation of OpenSID, such as increased community participation, improved information accessibility, and greater efficiency in delivering public services. Challenges encountered during the implementation, such as limited resources and technical knowledge, are also discussed. In conclusion, the digital transformation of villages using OpenSID holds great potential in enhancing the quality of life for communities, fostering public participation, and delivering more effective services. Kedungdowo Village is expected to serve as an inspiration for other villages to embrace digital transformation as a step towards a more advanced and inclusive village.